Development and evaluation of a biomass-fired micro-scale CHP with organic rankine cycle - Shao, Yingjuan (2011)
Combined Heat and Power Generation (CHP) or cogeneration has been considered worldwide as the major alternative to traditional energy systems in terms of signi ticant energy saving and environmental conservation. A renewable energy resource-fuelled CHP would deliver even more environmental benefits than a fossil tuel-driven CHP. Biomass is one of the renewable energy resources that plays an important role to the world primary energy supplies and can be used to fuel CHP systems. Many medium- and large-scale biomass-fired CHP plants have been demonstrated and commercialized in the world. However, biomass-fuelled microscale CHP (1-1 OkW c> which is suitable tor building applications has yet to be commercialised or demonstrated. The development and evaluation of a micro-CHP system operating on biomass energy has been the focus of this PhD research. It is an integral part of an externally funded research project which aims to develop and evaluate a novel, first-of-its-kind, micro-scale (l - 2 kWe) biomass-tired CHP system suitable for public and large domestic buildings' applications. The specific tasks of the present PhD research arc: To thermodynamically model the micro-scale biomass-fired CHP system with organic Rankine cycle (ORC): different environment-friendly working fluids are to be modelled with the ORC processes. To experimentally evaluate the micro-scale biomass-tired CHP system in terms of power generation and combined heat and power pertormance. To experimentally investigate the combustion performance and NOx emissions of the biomass pellet boiler which is a key component of the micro-scale biomass-fired CHP system. The micro-scale biomass-tired CHP system with ORC developed by the research team of University of Nottingham including the author of this PhD thesis mainly consists of a biomass boiler, an ORC fluid evaporator, an ORC turbine, an alternator, a heat reeouperator and a condenser. The boiler produces hot water which transfers heat to the organic working tluid via the evaporator. The generated organic fluid vapour drives a turbine to rotate an alternator, producing power. The expanded organic fluid vapour leaving the turbine transfers some of its heat to the recouperator and then is condensed by cooling water which can be heated to around 40 - 50 °C for domestic washing and under-floor heating purposes. The main methodologies of the present PhD research are the thermodynamic modelling of the proposed micro-scale biomass-tired CHP system with ORC and the laboratory testing of the assembled micro-scale biomass-fired CHP system and its main components (biomass boiler, ORC turbine, alternator, heat exchangers etc.). Literature review has demonstrated that the biomass-fired micro-CHP systems for buildings present many advantages compared to conventional separate heating and power supply systems (e.g. a dedicated boiler for heating and grid for power supply) as they can present higher primary energy savings and lower CO2 emissions. ORC is a suitable thermodynamic cycle that could be used for micro-CHP systems while operating with waste heat and renewable energy resources which are available at relative low temperatures. Thermodynamical modelling of the proposed micro-scale biomass-fired CHP system with ORC has been carried out and the results have been presented and discussed in the thesis. Three different environment-friendly working fluids, namely HFE7000, HFE7100 and n-pentane, have been modelled with various ORC process configurations. The laboratory testing of the assembled micro-scale biomass-fired CHP system and its main components (biomass boiler, ORC turbine, alternator, heat exchangers etc.) has been carried out initially with a 25kW biomass boiler and then with a 50kW biomass boiler. The main purpose of the laboratory testing has been to evaluate the main energy efficiencies (the electrical efficiency and the total CHP efficiency) of the assembled micro-CHP systems. The combustion performance and NOx emissions of each biomass boiler have also been investigated as the biomass boiler is a key component of the micro-scale biomass-tired CHP system. The experimental findings of these laboratory tests are presented and analysed in the thesis. Finally, the conclusions of the present PhD research have been given. The modelling results have shown that the electrical efficiency of the micro-CHP system depends on not only the modelling conditions but also the ORC fluid. A comparison of the three fluids generally follows the following order: n-pentane > HFE7000 > HFE7100. For the laboratory test, the 25kW biomass boiler-driven micro-CHP system, having an ORC efficiency in the range of 2.20% - 2.85%, can generate electricity of 344.6W and heat of 20.3kW, corresponding to electricity generation efficiency 1.17% and CHP efficiency 86.22%. And the 50kWth biomass boiler-driven micro-CHP system, having an ORC efficiency of 3.48% - 3.89%, can generate electricity of 748.6W and heat of 43.7kW, corresponding to electricity generation efficiency 1.43% and CHP et1iciency 81.06%.